The Obligatory Bequest in (Kashf al-Ghawamid Sharh Manzumat Qatr al-Aridh in the Science of Inheritance, by al-Nawdhi): A Sharia Study Comparatively with Iraqi Law and its Applications in Kurdistan - Amin, Prof. Dr. Mustafa Muhammad; Ahmed, Asia Abdullah (Sulaimani Journal for Humanities, 2024)
Sheikh Ma'ruf al-Nawdahi authored his book entitled "Kashf al-Ghawamid: A Commentary on the Poem 'Qatr al-'Aridh' in the Science of Inheritance." The poem "Qatr al-Nada" was originally written by the Sheikh on the science of inheritance. He then wrote "Kashf al-Ghawamid," explaining his poem "Qatr al-'Aridh" in the science of inheritance. This book is considered one of the most important works on the science of inheritance. His approach in writing the book was to adopt the Shafi'i school of thought in matters where there was disagreement among jurists. I have selected some verses of poetry from the manuscript and explained them, which relate to the inheritance of grandchildren and the obligatory bequest, as these are frequently asked questions and often lead to family disputes. For example, when a son dies leaving children, and then his father dies, the legal division of the estate issued by the regional courts will grant them a share of their grandfather's inheritance under the name of the obligatory bequest. However, Sheikh al-Nawdahi and the majority of Kurdish scholars do not accept the obligatory bequest, arguing that inheritance is based on the strength of kinship, with a son being closer than a grandson. It hides him.